The relationship between corporate governance mechanisms and the performance of Saudi listed firms - Mamdouh Abdulaziz Saleh Al-Faryan (Corporate Ownership & Control, 2017)
This paper gauges, both qualitatively and quantitatively, the pertinent variables to corporate governance practices and their relationship to business productivity in the context of the Kingdom of Saudi Arabia. This study was conducted in response to the limited literature in this context. A new code of corporate governance was issued by the Saudi Arabian Capital Market Authority as a direct consequence of the 2006 stock market crash; in 2010, the code was made mandatory for listed firms. Rigorous empirical studies are practical not only for Saudi Arabia and its policy makers but also potentially for solving global investment issues and ensuring security. This study found two variables to have a significant negative relation: chief executive officer turnover and independent board members. Thus, greater rates of chief executive officer turnover are associated with negative firm performance. In addition, independent board directors' negative value was found to be very close to zero and significant only at the 10% level. Consequently, some caution is required when considering this result.
Keywords: G10; G30; G34; L25; 330; Corporate Governance; Firm Performance; Saudi Arabia; Stock Market